"Crack lung" caused by an impure preparation. Issue 9 (September 1996) - Kon, O. M.; Redhead, J. B.; Gillen, D.; Fothergill, J.; Henry, J. A.; Mitchell, D. M.
Abstract : Pulmonary complications of crack cocaine have been reported mainly from American centres. Crack usage is now on the increase in the UK. Three cases of "crack lung" are reported in patients who acquired the drug from the same source. The pulmonary syndrome they developed was due to an impure form of crack.